Project Based Learning (PjBL) Learning Model with STEM Approach in Natural Science Learning for the 21st Century - Ika Rahmania (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The writing of this paper aims to discuss the learning of PjBL with the STEM approach to science learning in the face of the demands of the 21st century. The science learning model that is in accordance with the STEM approach is one of the Project Based Learning learning models. The STEM learning model with STEM approach is project-based learning by integrating STEM fields that can provide students with opportunities for contextual learning through complex activities such as exploring planning learning activities, implementing projects collaboratively, and ultimately producing a product outcome. The purpose of this paper will also describe the concept of STEM and the implementation of the STEM approach to science learning. The method used in this paper is a literature review by selecting several articles and journals regarding the STEM approach and its implementation in junior secondary education. In addition, a basic curriculum competency study of 2013 was conducted at the junior high school level that could be integrated into the STEM approach. The results of the study show that some basic competencies at the junior secondary school level in science learning can be integrated with the STEM approach in the form of activities to familiarize the STEM approach in the classroom and the provision of projects to students. Thus the implementation of the STEM approach at the junior secondary school level in science learning can be done in Indonesia in order to prepare competent human resources in facing the challenges of the 21st century. The Pjbl approach and STEM can shape students into human resources who are capable of critical and creative thinking, systematic and logical so as to be able to meet 21st century human resource standards and be able to face increasingly complex global challenges.